Auditoria de cumplimiento a los programas y proyectos del patronato de amparo social del Gad La Mana año 2018 - Zurita Chavarria, Diana Angélica (2019)
This research is focused on an audit of compliance, which is the verification or examination of the financial, economic, administrative, operations and of any kind of an entity, to establish that they have made in accordance with the rules legal, regulatory, statutory and existing procedures that apply to you (Ramírez, 2017). In addition, the approach is based on programs and projects which are actions aimed at accomplishing a goal. The objective of the research is to run a compliance audit programs and projects on the Board, allowing you to find solutions for the problems detected. The legal regulations of the research is based on the issues of the organization. This research was based with the theoretical framework through the criterion of different authors that validated the study process. The methods that were used have a qualiquantitative approach which allowed to develop the research, using deductive, inductive, analytic and historical-logical methods. The results of the investigation show that the Board complies with the laws and legal regulations. Finally, the evaluation of internal control obtained a high of 90% confidence level and a low risk of 10% level. Elaborate recommendations include implementing a risk plan to mitigate and having sufficient funding to external factors that affect the Board of Trustees, in addition to developing quarterly budget control. Key words: Compliance audit, programs and projects, Internal Control